New OprM structure highlighting the nature of the N-terminal anchor - MONLEZUN, Laura; Phan, Gilles; Benabdelhak, Houssain; LASCOMBE, Marie-Bernard; NTSOGO ENGUENE, VERONIQUE YVETTE; Picard, Martin; Broutin, Isabelle (Frontiers in Microbiology, 2015)
Among the different mechanisms used by bacteria to resist antibiotics, active efflux plays a major role. In gram-negative bacteria, active efflux is carried out by tripartite efflux pumps that form a macromolecular assembly spanning both membranes of the cellular wall. At the outer membrane level, a well-conserved Outer Membrane Factor (OMF) protein acts as an exit duct, but its sequence varies greatly among different species. The OMFs share a similar tri-dimensional structure that includes a beta-barrel pore domain that stabilizes the channel within the membrane. In addition, OMFs are often subjected to different N-terminal post-translational modifications, such as an acylation with a lipid. The role of additional N-terminal anchors is all the more intriguing since it is not always required among the OMFs family. Understanding this optional post-translational modification could open new research lines in the field of antibiotics resistance. In E. coli, it has been shown that CusC is modified with a tri-acylated lipid, whereas TolC does not show any. In the case of OprM from Pseudomonas aeruginosa, the N-terminal modification remains a matter of debate, therefore, we used several approaches to investigate this issue. As definitive evidence, we present a new X ray structure at 3.8Å resolution that was solved in a new space group, making it possible to model the N-terminal residue as a palmitylated cysteine.